A Public World Without Public Relations? - Nayden, Nikolay (Javnost-The Public, 2009)
The term “public relations” (PR) has long gained currency as meaning the practice of producing a positive public image. This article argues that public relations should be released from the prison of “PR” and, instead, reconceptualised as relations which define the public realm much as economic relations define the economy. From this point of view, three main levels of public relations can be distinguished: (1) relations between public institutions, (2) relations between citizens and public institutions, and (3) relations between single citizens who communicate as strangers. Relations on the last level are qualifi ed as “basic public relations” because they are the simplest, reproduce at all levels, do not need institutional mediation, and are the nucleus of all political roles and meanings. Freeing the term “public relations” from its restricted usage to mean “relations in public” makes it possible to discover the common roots of political institutions and the public sphere and to explore the innate kinship between politics and all other segments of public life. The overall eff ect is a re-conceptualising of politics as quintessentially stemming from public relations and of democracy as the very essence of politics.